Verità dell’essere e verità dell’arte. Adorno contra Heidegger - Magno, Emanuela (Scenari, 2021)
The contribution aims to face the difficult Heidegger/Adorno contest on the topic: The Truth of Art. This is an argument which appears “asymmetric”, since it starts from Adorno’s critique to Heidegger’s doctrine of Being, which can be found in Negative Dialectics. The distance between the two philosophers is then framed and included within the field of Art, which is an elected point of view because both philosophers recognize that here dwells the ultimate destination of truth.